Proposal for a Management Indicator of the Capability of Organizations for the Development of Sustainable Innovations - Galvez-Manriquez, D; Santander-Tapia, P; Delgado-Cadena, L (Springer Nature, 2025)
Innovation allows organizations to generate new solutions that add value, provide competitive advantages and enable economic growth. However, the current challenges embodied in the 17 Sustainable Development Goals, such as climate change, poverty, health, hunger, education, among others, force innovation to consider not only economic factors, but also social and environmental factors. This is how the concept of sustainable innovation arises, which seeks to integrate three factors: economic, social and environmental. This article proposes a model for managing the capability of organizations to develop and implement sustainable innovations that have this triple impact. Based on a model of best practices evaluated from maturity grids, the potential of organizations to carry out sustainable innovation is diagnosed. The objective is that this diagnosis serves as a starting point to propose improvement strategies in this aspect. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.